Re-assemblage and Dispersal: Exploring the Agency of Etruscan Votive Bronze Figurines in Museum Collections (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2024)
The document investigates the evolving role of museum collections, particularly through the lens of ‘re-assemblage’, which involves studying the histories and contexts of artefacts. Focusing on Etruscan votive bronze figurines from the British Museum and the Metropolitan Museum of Art, the research reveals how these objects, despite losing their original archaeological settings, continue to possess agency and accrue new meanings as they are collected and dispersed. Ultimately, the paper underlines that museum collections remain fluid and are subject to constant reinterpretation and renewal of value over time. Il contributo analizza il ruolo in evoluzione delle collezioni museali, in particolare attraverso la lente del ‘riassemblaggio’, che implica lo studio della storia e del contesto dei manufatti. La ricerca si concentra sulle statuette votive etrusche in bronzo provenienti dal British Museum e dal Metropolitan Museum of Art e rivela come questi oggetti, pur avendo perso il loro contesto archeologico originale, continuino a possedere un'agency e acquisire nuovi significati man mano che vengono raccolti e dispersi. In definitiva, il documento sottolinea che le collezioni museali rimangono fluide e sono soggette a una costante reinterpretazione e al rinnovamento del valore nel corso del tempo.
Keywords: Museum collections; Re-assemblage; votive bronze figurines; Etruscan archaeology; Cultural heritage